Mudaraba as a Model of Islamic Finance - Nidaussalam, M (Shirkah: Journal of Economics and Business, 2016)
Sharia bank has mostly been determined by its absent of rate transaction which is officially decided in agreement between the bank and its customer (akad). Mudharaba, one of the akad variants, offers equity finance requiring profit and loss sharing (PLS). This paper aims to critically discuss the principles of mudharaba commitment, mainly focusing on the process of funding and financing. To argue, mudharaba is an cooperating commitment between two economic agencies for which the first agency expected to provide financial capital while the other takes a part in managerial work-progress. In this process, the more profit for mudharib the more profit for the investor.      Keywords: mudharaba, islamic finance, profit and loss sharing